Compatibility characterization of Gentamicin-Nigella sativa fusion as a future greener pharmaceutical intended for ortheopaedic infection - Harun Ismail, Ahmad Fahmi; Mohamed, Farahidah; Mohd Yusof, Nazri; Mohd Shafri, Mohd Affendi (2014)
The medical potentials of natural product have been extensively exploited nowadays to reduce many adverse effects associated with the conventional medicine. However, the issue of compatibility has become a major concern amongst the researchers in developing any drugs and active pharmaceutical ingredients. In this study, the fusion between the oil of Nigella sativa L. (or Habbatus Sauda) and gentamicin powder was sent for sterilization using gamma irradiation at 10 kGy - 40 kGy. This fusion was developed and intended to be used for the treatment of osteomyelitis. The pre and post gamma irradiation evaluation was carried out by using Fourier Transform Infrared Spectroscopy (FTIR) to observe for any physical changes both for the raw materials and the fusion. The data from Differential Scanning Calorimeter (DSC) was parallel with FTIR in indicating no physical and chemical interactions initiated during the process of sterilization. For DSC, this was done by conforming the melting point of pre and post gamma irradiation for both gentamicin powder and N. sativa oil. Nonetheless, the fusion was not able to be evaluated using DSC due to rapid disintegration of the oil when subjected to a temperature higher than 120o C. In addition, the surface and the interfacial tensions between the oil and the gentamicin solution were measured to support the pre and post evaluation of gamma irradiation on the API. The N. sativa oil was further evaluated by using Thin Layer Chromatography (TLC) to observe the retention factor (Rf) for both pre and post gamma irradiation by employing the mobile phase of dichloromethane and hexane (1:1). The Rf value showed similarity for N. sativa oil in both conditions indicating the oil was stable enough to undergo the gamma sterilization. Gentamicin however could not be evaluated using TLC due to the issue of insolubility in any organic solvents. . Encapsulation of N. sativa oil by using FDA-approved polymer, PLGA, was carried out to formulate the sustained release microparticles. The encapsulation was carried out by employing the single emulsion solvent evaporation method. Having the characteristic of biodegradable and biocompatible in nature, PLGA is the best candidate to be used as the encapsulating agent. Three different parameters were studied i.e. the molecular weight of PLGA, the method of homogenizing and the amount of N. sativa oil loaded during the fabrication process. The external morphology and the particle size were observed and analyzed by using scanning electron microscopy (SEM) and laser diffraction respectively. The size of the fabricated particles ranging from 5.83 µm ± 0.04 up to 147.71 µm ± 3.18 was observed mostly with smooth but irregular shape. Furthermore, the percentage of oil loading for every formulations was evaluated by using spectrophotometry with the highest loading was recorded at 91.90 % and the lowest with the value of 56.94%. However, the oil loading from two formulations were unable to be evaluated due to the particle stability and the degree of hydrophobicity issues. Manipulating the potential of this fusion is believed to open a new promising method in treating osteomyelitis. Taking into consideration the ability to encapsulate the N. sativa oil by using PLGA, this ongoing research can provide an envision towards the possible 'greener' opportunities to be explored in future.